Optimization of fibrinolytic protease production from Bacillus subtilis I-2 using agro-residues - Bijender Kumar Bajaj; Satbir Singh; Mowkshi Khullar; Kaurab Singh; Shikha Bhardwaj (Brazilian Archives of Biology and Technology, 2014)
The aim of this work was to study the production of fibrinolytic protease by Bacillus subtilis I-2 on agricultural residues. Molasses substantially enhanced (63%) protease production (652.32 U/mL) than control (398.64 U/mL). Soybean meal supported maximum protease production (797.28 U/mL), followed by malt extract (770.1 U/mL), cotton cake (761.04 U/mL), gelatin (742.92 U/mL) and beef extract (724.8 U/mL). Based on the Plackett-Burman designed experiments, incubation time, soybean meal, mustard cake and molasses were identified as the significant fermentation parameters. Ammonium sulfate precipitation and DEAE sephadex chromatography resulted 4.8-fold purification of protease. Zymography showed the presence of three iso-forms in the partially purified protease preparation, which was confirmed by the SDS-PAGE analysis (42, 48, 60 kDa). Protease exhibited maximum activity at 50oC and at pH 8.0. Significant stability was observed at 30-50oC and at pH 7.0-10.0. Mg2+, Zn2+, Co2+, Ca2+, Mn2+ and Cu2+,EGTA, EDTA and aprotinin severely decreased the enzyme activity.